Drafting mechanisms between a dolphin mother and calf. (7th October 2015) - Shoele, Kourosh; Zhu, Qiang
Abstract: We numerically study the drafting mechanisms between a dolphin mother and her calf swimming near the free surface. Formation locomotion between the cetacean mother-calf pair provides a way for the mother to assist the calf in its locomotion. Depending on the age and size of the calf, it swims at neonate, echelon, and infant positions. At each position, the effects of the calf's size, swimming speed, proximity to the free surface and the formation pattern are investigated and the optimal configurations predicted by the model based on the swimming hydrodynamics are compared with previous observations. It is shown that the neonate position is the optimal formation for controlling the separation of the calf, and the echelon position is the most hydrodynamically efficient position in transferring the thrust force from the mother to the calf. The infant position, on the other hand, avoids the energy loss due to wave generation so that it improves the self-propulsion performance of an older calf. Highlights: We model the drafting mechanism between a dolphin mother and calf beneath the free surface. We examine how formation pattern changes the hydrodynamic forces as well as the drafting efficiency of the calf. A newborn calf hydrodynamically benefits by swimming close to the free surface in the neonate position, slightly above its mother flank. A mother increases her swimming speed after the birth to prevent separation of her calf. We quantitatively show why older calves more routinely swim in the infant position than the echelon position.